The Concept and Future of Electronic Voting in Election Systems - Subekti, Dimas (Politika: Jurnal Ilmu Politik, 2025)
The purpose of this study is to explain the development of research on the topic of e-voting. This research uses a qualitative method using a scoping review approach. Documents retrieved in the Scopus database are limited from 2013-2023. The findings of this study show that the development of research on e- voting has a significant impact on the dynamics of various countries that organize elections. Theoretically, the mapping of research on e-voting is inseparable from the concepts of e-democracy and e-government. This illustrates that the application of e-voting is a consequence of technological developments in politics that require countries to modernize the democratic system to form and run the government legally. Furthermore, practically speaking, for future research on this topic, taking the point of view of e-voting machines is a huge opportunity and greatly contributes to the development of this method of implementation in all countries that adhere to democratic systems.